2020
DOI: 10.1063/5.0033849
|View full text |Cite
|
Sign up to set email alerts
|

The motion of respiratory droplets produced by coughing

Abstract: Coronavirus disease 2019 has become a global pandemic infectious respiratory disease with high mortality and infectiousness. This paper investigates respiratory droplet transmission, which is critical to understanding, modeling, and controlling epidemics. In the present work, we implemented flow visualization, particle image velocimetry, and particle shadow tracking velocimetry to measure the velocity of the airflow and droplets involved in coughing and then constructed a physical model considering the evapora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 52 publications
5
35
2
Order By: Relevance
“…In this study, we performed two experiments in different oxygen delivery modes and modalities. Based on the particle visualization study, we found that visible droplets reached 60–80 cm while speaking and 1 m while coughing in a sitting position; the findings are similar to those in a recent study (13). In addition, these findings support results in a systematic meta-analysis, which showed that a physical distance of 1 m or more is optimum to reduce person-to-person virus transmission and to keep healthcare workers from contracting the SARS-CoV-2 infection (14).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we performed two experiments in different oxygen delivery modes and modalities. Based on the particle visualization study, we found that visible droplets reached 60–80 cm while speaking and 1 m while coughing in a sitting position; the findings are similar to those in a recent study (13). In addition, these findings support results in a systematic meta-analysis, which showed that a physical distance of 1 m or more is optimum to reduce person-to-person virus transmission and to keep healthcare workers from contracting the SARS-CoV-2 infection (14).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, an evaporation model 39 is implemented to model the mass and the diameter ( D ) change of droplets as follows: where D is the droplet diameter, M L is the molecular weight of water (0.018 kg/mole), is the average diffusion coefficient for vapor molecules in the saturated film around the droplet, 998 is the density of water, J/(mol K) is the gas constant, T f is the temperature in the saturated film around the droplet, Re is Reynolds' number, Sc is Schmidt's number, and is the difference between the vapor pressure near the droplet and that in the ambient atmosphere. According to a recent study, 40 this model can estimate well the evaporation of cough-generated droplets in motion. These parameters are dependent on the environment temperature T and relative humidity ( RH ), which are chosen as 20 C and in this study, representing a winter indoor environment approximately.…”
mentioning
confidence: 97%
“…The oval shape deformation of the droplet cloud can be explained as a result of different advancing and settling velocities of droplets of different sizes. 21 At t = 2.0 s, the cloud drops approximately to the waist height and deforms into an elongated shape that expands horizontally for both cases. Significant differences between the two cases are observed starting from this instant.…”
mentioning
confidence: 91%